2007
DOI: 10.1080/16513860701673892
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual spoken word recognition by children with cochlear implants

Abstract: This study examined how prelingually deafened children with cochlear implants combine visual information from lipreading with auditory cues in an open-set speech perception task. A secondary aim was to examine lexical effects on the recognition of words in isolation and in sentences. Fifteen children with cochlear implants served as participants in this study. Participants were administered two tests of spoken word recognition. The LNT assessed isolated word recognition in an auditoryonly format. The AV-LNST a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 21 publications
(25 reference statements)
2
3
0
Order By: Relevance
“…That is, the performance of the participants with HL on SWR in noise (SNR = -2 to 15 dB) was inadequate. Thus, in agreement with previous findings, school-aged children with HL experience critical difficulties in the SiN perception [6,[31][32][33][34][35][36][37][38]25,27,39,40,9], specifically when they had to recognize words through auditory-only modality [41][42][43][44]24,18,45,46]. However, their SWR scores increased stepwise in the SNRs from -2 to 15 dB (Figures 1-4).…”
Section: Discussionsupporting
confidence: 91%
“…That is, the performance of the participants with HL on SWR in noise (SNR = -2 to 15 dB) was inadequate. Thus, in agreement with previous findings, school-aged children with HL experience critical difficulties in the SiN perception [6,[31][32][33][34][35][36][37][38]25,27,39,40,9], specifically when they had to recognize words through auditory-only modality [41][42][43][44]24,18,45,46]. However, their SWR scores increased stepwise in the SNRs from -2 to 15 dB (Figures 1-4).…”
Section: Discussionsupporting
confidence: 91%
“…The ability to observe visual articulations in addition to hearing the speaker during a linguistic utterance significantly improves a listener’s speech perception performance in both quiet and in noise (Sumby & Pollack 1954; Erber 1975; MacLeod & Summerfield 1987; Grant & Seitz 2000; Bernstein et al 2004; Tye-Murray et al 2007a). Similar audiovisual benefit for speech perception performance has also been shown in individuals with CIs (Kaiser et al 2003; Rouger et al 2007; Kirk et al 2007). Despite the acknowledged role of vision in shaping speech perceptual abilities, the current gold standard for the clinical quantification of CI benefit is the assessment of speech perception skills administered in an auditory-only format (Hay-McCutcheon et al 2009).…”
Section: Introductionsupporting
confidence: 68%
“…One likely reason for these deficits is that individuals who receive a cochlear implant (CI) at an early age utilize a modified auditory signal to develop spoken language skills, given that CIs rely on a limited number of independent channels to stimulate groups of surviving auditory neurons. Thus, pre-lingually deafened individuals must rely more heavily on information from other sensory modalities such as vision to develop expressive and receptive language (Lachs et al 2001; Kirk et al 2007). Increased reliance on visual cues and lip reading for understanding spoken language likely results in the development of audiovisual integration and visual-only processing abilities that are different from individuals with normal hearing.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown an advantage in speech reception by CI users with audiovisual presentation compared to auditory-only or visual-only (speechreading) information (Bergeson, Pisoni, & Davis, 2005; Geers, Brenner, & Davidson, 2003; Kaiser, Kirk, Lachs & Pisoni, 2003; Kirk, et al 2007; Rouger et al, 2007; Rouger, Fraysse, Deguine, & Bagone, 2008). That work suggested that the audiovisual advantage derives from CI users having acquired both better speechreading ability and greater ability to integrate the visual information with the distorted speech signal.…”
mentioning
confidence: 97%